2015
DOI: 10.1007/s10439-015-1478-1
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Biological Modification of Polycaprolactone Electrospun Nanofiber by Panax Ginseng Extract for Bone Tissue Engineering Application

Abstract: Medicinal plants as a therapeutic agent with osteogenic properties can enhance fracture-healing process. In this study, the osteo-inductive potential of Asian Panax Ginseng root extract within electrospun polycaprolactone (PCL) based nanofibers has been investigated. Scanning electron microscopy images revealed that all nanofibers were highly porous and beadles with average diameter ranging from 250 to 650 nm. The incorporation of ginseng extract improved the physical characteristics (i.e., hydrophilicity) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…7 Many studies have reported that various synthetic and natural polymers, including polycaprolactone, PLGA, collagen and chitosan, have been electrospun to fabricate potential bone scaffolds that are utilized as cell-supporting matrices for bone repair. [8][9][10] PLGA is one of the most promising degradable materials and attractive for tissue engineering applications due to its good mechanical properties, adjustable degradation rate, low immunogenicity, and acquisition of FDA approval for human therapy. 11,12 PLGA-based electrospun nanobrous scaffolds have been used for engineering a wide range of tissues such as skeletal muscle, cartilage and bone tissues.…”
Section: Introductionmentioning
confidence: 99%
“…7 Many studies have reported that various synthetic and natural polymers, including polycaprolactone, PLGA, collagen and chitosan, have been electrospun to fabricate potential bone scaffolds that are utilized as cell-supporting matrices for bone repair. [8][9][10] PLGA is one of the most promising degradable materials and attractive for tissue engineering applications due to its good mechanical properties, adjustable degradation rate, low immunogenicity, and acquisition of FDA approval for human therapy. 11,12 PLGA-based electrospun nanobrous scaffolds have been used for engineering a wide range of tissues such as skeletal muscle, cartilage and bone tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The wettability (contact angle) of each PBSGL n nanofibrous membrane was evaluated by applying the sessile drop technique (with distilled water) using a VCA Optima Surface Analysis system (AST products, Inc., Billerica, MA, USA) at ambient conditions. In vitro mass loss of the PBSGL n membranes was measured after 60 days, as we previously described 66 .…”
Section: Methodsmentioning
confidence: 99%
“…The rabbit bone marrow-derived MSC metabolic activity (proliferation) on each PBSGL membrane (3 cm × 3 cm) was evaluated using a colorimetric 3-(4, 5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2(4-sulfophenyl)-2H tetrazolium (MTS) assay (Promega, Madison, WI, USA), as we previously described 66 . Briefly, PBSGL membranes were sterilized by soaking in 100× sterilizing solution containing penicillin G (10,000 U/ml), streptomycin (10,000 µg/ml), and amphotericin B (250 µg/ml) overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ginseng root extract was added in electrospun polycaprolactone (PCL) nanofibers to enhance the expression of osteogenic genes in MSC. The incorporation of ginseng root extract in electrospun PCL scaffolds also improved its hydrophilicity and accelerated degradation rate . CQ extract was directly blended with chitosan/Na‐carboxymethyl cellulose scaffolds to enhance the ALP activity of Saos‐2 osteosarcoma .…”
Section: Introductionmentioning
confidence: 99%